A Systems study on the Airline Catering Operation of Philippine Airlines (PAL) Passenger Services Department - Almendral, Ma. Luisa; Bañez, Ricarda; Lorenzo, Lowell; Pasion, Amado Jr; Sapico, Reynaldo; Singson, Rogelio (College of Engineering, 1983)
This paper is a system study on the airline catering operation of PAL's Passenger Services Department. The system of interest covers the Warehousing, Receiving of IFC Stores and the Production Section. The cycle of operation begins with the receipt of the menu from the airline, ending with its delivery. Within the cycle, IFC Stores is concerned with the requisition of materials requirement for Production. The procurement of these needed materials is done thru the centralized Purchasing Department of PAL. Delivery and storage is again handled by IFC Stores until the materials are withdrawn for Production?s use. Production prepares the meals that have to be delivered on time for the plane?s departure. The system was documented through interviews. No written objectives of each subsystem were available that the group had to come up with its own objectives based on their perception of what it should be. After which, indicators of the performance of the system were determined but then no historical data about these indicators could be produced, hindering a proper evaluation of the system?s performance. Thus, the problems identified were based on deductions, inferences and observations; their range and gravity cannot be given. These problems are the following: 1) Uncertainty that the imported supplies purchased is the most economical. In as much as bidding is not done for these materials, the Purchasing Department is responsible for choosing the best supplier in terms of cost, quality and reliability. Presently, however, the Executive Chef dictates the supplier, bypassing the authority of Purchasing and leaving no check on the said supplier. 2) Unsystematic quality inspection procedures. According to the receiving personnel, 100% inspection is the present quality control procedure for incoming raw materials. However based on an incident witnessed by the group, it seems that this policy is not strictly followed. Furthermore, there are a lot of acknowledged disadvantages with this policy. 3) Unsystematic determination of order quantity. Ordering of materials requirements is based on 100% booking of flight. Despite this standard, frequent stock outs still occur. As a result, a large amount (P10,000) is allotted for petty cash disbursement in case immediate materials needs are unavailable. 4) Frequent delays in Production. Volume of production depends on the number of passengers booked. This information is received from the airline and is subject to changes due to cancellation and addition of bookings, sometimes leaving production no time to cope with the changes. Stock out contributes to the delay, too. Included in the analysis are input-output diagrams of each system component to distinguish the variables and the parameter in the information flow. This, in turn, was used in attacking the controllable causes of the problems to create the system design. The system design begins with the incorporation of a Materials Planning and Control Department within the system of interest. This department is primarily concerned with the planning and monitoring of the material requirement of Production. One of its immediate tasks is the design of an inventory control policy and a quality control procedure that would fit the needs of the system. To accomplish this, the proper management of information is very vital. Its On-Line computer system must be fully utilized as the voluminousness of the data requires it so. No specific model for the design was yet recommended as historical data was sadly lacking. However, the study enumerates the consecutive steps to be taken to give MPC a starting push. Several models are also listed for their convenience. Another major component in the system design is the monitoring of the SOI's performance through monthly reports to top management. With the corresponding lists of the measure of performance of each component, relevant data can now be gathered and recorded to gauge their efficiency. The documentation of all materials' quality standard is another recommendation to facilitate quality inspection and to avoid unwarranted rejection of delivered materials due to flimsy excuses by the executive chef. Revision in the forms flow was also done. Finally, prioritized steps for the implementation of the designs and recommendation are given in the conclusion.